Transaction Cost Analysis of ASEAN Food Security Cooperation on Rice Commodity - Pinasthika, Reni Erlita (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2024)
Food Security Cooperation was implemented by ASEAN through the ASEAN Economic Community (AEC), focusing on regional market integration. The food security index of its members has not been strengthened beyond the global index through this cooperation.